(untitled) (Journal of Nepal Physical Society, 2021)
In order to apply muon spin rotation and relaxation method for study of life sciences like electron transfer process, detection of molecular concentration, photosynthesis process, etc., theoretical study to understand the stopping sites of muon and its charge species in the macromolecules is necessary. In the systematic theoretical study to know the behaviour of muon and muonium in water hydrated biological macromolecules like protein and DNA through the first-principles approach, the behaviour of a water molecule in the presence of muonium in histidine amino acid with extended main chain is presented here. The sites of a water molecule and a muonium in histidine amino acid are estimated. Two possible sites with potential energy 0.3 eV (approximately) for water molecule in the optimized structure of muonium in extended main chain histidine were estimated. Water in the sites is expected to contribute to enhance the intra- and inter-chain electron transfer in the system as reported experimentally.